Alder-induced stimulation of soil gross nitrogen turnover in a permafrost-affected peatland of Northeast China. (September 2022) - Ramm, Elisabeth; Liu, Chunyan; Mueller, Carsten W.; Gschwendtner, Silvia; Yue, Hongyu; Wang, Xianwei; Bachmann, Juliane; Bohnhoff, Joost A.; Ostler, Ulrike; Schloter, Michael; Rennenberg, Heinz; Dannenmann, Michael
Abstract: For the prediction of permafrost nitrogen (N) climate feedbacks, a better process-based understanding of the N cycle in permafrost ecosystems is urgently needed. Therefore, we characterized and quantified soil organic matter, gross soil microbial ammonification and nitrification and soil-atmosphere exchange of nitrous oxide (N2 O) of boreal permafrost ecosystems on the southern edge of the Eurasian permafrost area in situ . Soil organic carbon (SOC) and total nitrogen (TN) stocks (top 0.5 m) of tree-free lowland peatland (LP) soils exceeded those of gravel-rich upland forest (UF) soils by an order of magnitude. Nuclear magnetic resonance spectroscopy revealed more recalcitrant organic matter at greater depth and more bioavailable organic matter substrates in upper peat horizons. In line with this result, gross ammonification and nitrification generally decreased with increasing sampling depth. Gross rates of mineral N turnover in active layers were comparable to those of temperate ecosystems. Despite substantial gross ammonification, the low nitrification:ammonification ratios and negligible soil N2 O emissions depicted however a closed N cycle at UF and LP characterized by N limitation. In strong contrast, the lowland peat soils underneath alder trees (LA), being associated with diazotrophic bacteria in root nodules, showed an accelerated N turnover with very high gross rates of ammonification (3.1 g N m −2 d −1 ) and nitrification (0.5 g N m −2 d −1 ), exceeding those of UF and LP soils by an order of magnitude. This was accompanied by substantial N2 O emissions comparable to temperate agricultural systems or tropical forests. The increase in gross soil microbial ammonification and nitrification was most pronounced in the rooted soil layer, where N inputs from biological N fixation almost doubled TN concentrations and halved SOC:TN ratios. The frozen ground of LA contained strongly increased ammonium concentrations that might be prone to release upon thaw via subsequent nitrification. This study shows that alder forests that further expand on permafrost-affected peatlands with global change create hot spots of soil mineral N turnover, thereby potentially enhancing permafrost N climate feedbacks via N2 O emissions. Highlights: Boreal permafrost ecosystems of NE China show large gross nitrogen mineralization. Nitrogen limitation is released by alder-associated biological nitrogen fixation. Alder forests are hot spots of nitrification and N2 O emissions. Results suggest increasing N2 O-induced permafrost nitrogen climate feedbacks.